Safety and Compliance to Purified Vero Cell Intradermal Rabies Vaccine Given as Pre Exposure Prophylaxis among Veterinary College Staff and Students in Bangalore: A Descriptive Study - N R Ramesh Masthi; DH Ashwath Narayana; Divya Bharathi G; Isloor S; Sharada R R; Deekshith Reddy; Apoorva N; Parvesh Pasha (RGUHS National Journal of Public Health)
Background Rabies Pre-Exposure Prophylaxis PrEP eliminates the risk of rabies and therefore it is important for it to be administered to all individuals at risk. Hence this study was undertaken to vaccinate veterinarians and ensure they completed the PrEP schedule on time.Objectives The aim of the study was to assess the safety of purified Vero cell rabies vaccine PVRV pre-exposure prophylaxis administered via the intradermal route among students and faculty at a veterinary college in Bangalore.Methodology A descriptive study was conducted during the last quarter of 2024 among veterinary college students faculty and staff at the Government Veterinary College Bangalore. All the study subjects were administered a semi-structured questionnaire to assess their adverse reactions and compliance.Results A total of 101 subjects received rabies PrEP of which 14 subjects were faculty and 87 subjects were students. The median age of the study subjects was 24 years with IQR 9.7. The majority of the subjects 52 51.5 were males. Overall 13 12.9 subjects had reported one or more local adverse events while 5 4.9 subjects reported systemic adverse reactions during the course of PrEP i.e. three doses. The compliance to PrEP was found to be 97.Conclusion The intradermally administered PrEP vaccine was safe and the compliance was excellent.nbsp